The Impact of Social Media in Piano Practice Online Learning in the Covid-19 Pandemic Period - Setiawan, Afrizal Yudha; Habsary, Dwiyana; Bulan, Indra (Jurnal Seni Musik, 2021)
This research aims to examine and describe the design of practical online learning in the arts by utilizing social media as a platform to enforce lecturing activities during the Covid-19 pandemic, as well as the impact of the use of social media. The data was collected through focus group discussion, observations, interviews and documentation. The subjects involved in this research were 10 students who took major piano instruments in the Music Education Study Program at Lampung University. This research used qualitative methods, by analyzing interactive data. The results of the data analysis showed that the use of social media in piano online learning was able to increase student motivation through competitive strategies. The learning design by utilizing social media can be used as one of the strategies to overcome the lack of student learning motivation in practical learning in the arts during the Covid-19 pandemic.